Cigarette Smoking Is Associated With Lower Quadriceps Cross-sectional Area and Attenuation in Older Adults. Issue 6 (15th May 2019) - Marques, Elisa A; Elbejjani, Martine; Frank-Wilson, Andrew W; Gudnason, Vilmundur; Sigurdsson, Gunnar; Lang, Thomas F; Jonsson, Palmi V; Sigurdsson, Sigurdur; Aspelund, Thor; Siggeirsdottir, Kristin; Launer, Lenore; Eiriksdottir, Gudny; et al.
Abstract: Introduction: In addition to well-established links with cardiovascular and respiratory diseases, cigarette smoking may affect skeletal muscle; however, associations with quadriceps atrophy, density, and function are unknown. This study explored the associations of current and former smoking with quadriceps muscle area and attenuation as well as muscle force (assessed as knee extension peak torque) and rate of torque development—a measure of muscle power in older adults. Methods: Data from 4469 older adults, aged 66–95 years at baseline in the Age, Gene/Environment Susceptibility-Reykjavik Study with measurements of thigh computed tomography, isometric knee extension testing, self-reported smoking history, and potential covariates were analyzed. Results: Sex differences were observed in these data; therefore, our final analyses are stratified by sex. In men, both former smokers and current smokers had lower muscle area (with β= –0.10, 95% confidence interval [CI] = –0.17 to –0.03 and β = –0.19, 95% CI = –0.33 to –0.05, respectively) and lower muscle attenuation (ie, higher fat infiltration, β = –0.08, 95% CI = –0.16 to –0.01 and β = –0.17, 95% CI = –0.34 to –0.01, respectively) when compared with never smokers. Smoking status was not associated with male peak torque or rate of torque development. In women, current smoking was associated with lower muscle attenuation (β = –0.24, 95% CI = –0.34 to –0.13) compared to never smoking. Among female smokers (current and former), muscle attenuation and peak torque were lower with increasing pack-years. Conclusions: Results suggest that cigarette smoking is related to multiple muscle properties at older age and that these relationships may be different among men and women. Implications: This article presents novel data, as it examined for the first time the relationship between smoking and computed tomography-derived quadriceps muscle size (cross-sectional area) and attenuation. This study suggests that current cigarette smoking is related to higher muscle fat infiltration, which may have significant health implications for the older population, because of its known association with poor physical function, falls, and hip fractures.